2017
DOI: 10.1007/s00011-017-1032-8
|View full text |Cite
|
Sign up to set email alerts
|

The immunological function of CD52 and its targeting in organ transplantation

Abstract: Studies clearly showed that CD52 can modulate T-cell activation either by its intracellular signal pathways or by the interaction of soluble CD52 and Siglec-10 expressing on T cells. However, the regulatory functions of CD52 on other immune cell subpopulations in organ transplantation require to be studied in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 102 publications
4
72
0
1
Order By: Relevance
“…Anti-CD52 (alemtuzumab, lemtrada R ) is instead a humanized IgG1 monoclonal antibody (mAb) that eliminates CD52-expressing lymphocytes and generates a marked lymphopenia. Administration of this depleting mAb has been employed clinically for the treatment of lymphoma [3], the prevention of transplant rejection [4][5][6], and more recently it has been shown to efficiently inhibit relapses in MS patients [7,8]. CD52 is highly expressed on the surface of T and B lymphocytes and to a lesser extent on NK cells, monocytes, macrophages, DCs, eosinophils, and neutrophils [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-CD52 (alemtuzumab, lemtrada R ) is instead a humanized IgG1 monoclonal antibody (mAb) that eliminates CD52-expressing lymphocytes and generates a marked lymphopenia. Administration of this depleting mAb has been employed clinically for the treatment of lymphoma [3], the prevention of transplant rejection [4][5][6], and more recently it has been shown to efficiently inhibit relapses in MS patients [7,8]. CD52 is highly expressed on the surface of T and B lymphocytes and to a lesser extent on NK cells, monocytes, macrophages, DCs, eosinophils, and neutrophils [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…CD52 is highly expressed on the surface of T and B lymphocytes and to a lesser extent on NK cells, monocytes, macrophages, DCs, eosinophils, and neutrophils [9][10][11][12][13]. Although the function of CD52 on immune cells is still unclear, some evidence suggests that it may modulate T-cell activation and induce regulatory CD4 T cells [6]. Activated CD4 T cells with higher CD52 expression were able to suppress other effector T cells [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that Siglec-10 plays an important role in regulating the immune balance of in ammatory diseases. For example, the interaction of Siglec-10 and CD24 reduces the in ammatory response associated with the damage-associated molecular patterns (DAMPs) by inhibiting the activation of high mobility group box 1 (HMGB1) and NF-κB [15][16][17][18]. The interaction between Siglec-10 expressed on human DC and pseudaminic acid can increase the expression of IL-10 through MyD88 and p38 MAPK signaling pathway to promote anti-in ammatory function [19].…”
Section: Introductionmentioning
confidence: 99%
“…Virtually all T-PLL express CD52 and at a higher density than in other T cell and B cell malignancies [27]. Engagement of CD52 by alemtuzumab induces antibody-dependent cytolysis, activation of the complement system, and possibly direct apoptosis [28,29].…”
Section: Alemtuzumab Remains the Current Benchmarkmentioning
confidence: 99%